Contiguity Theory - Richards, Norvin (Book collections on Project MUSE., 2016)
Norvin Richards argues that there are universal conditions on morphology and phonology, particularly in how the prosodic structures of language can be built, and that these universal structures interact with language-specific properties of phonology and morphology.